Privatisation as a Worldwide Tool of Economic Reform: A Literature Review - Abdeldayem, Marwan Mohamed; Dulaimi, Saeed Hameed AL (International Journal of Social and Administrative Sciences, 2019)
This paper aims to present a general overview of the literature relating to privatisation as a worldwide economic phenomenon. It starts by describing the origins, definitions and the rationale for privatisation. The spread of the privatisation phenomenon throughout the world is also discussed. The study then provides justification for privatisation in less developed countries (LDCs). It also summarises privatisation objectives, the sequencing and pace of privatisation, factors influencing privatisation and the agent principal theory. The study then outlines the different privatisation methods and briefly refers to efficiency and effectiveness in the context of privatisation, privatisation and changes in corporate governance as well as arguments on privatisation. A discussion into the role of international agencies in the privatisation process is also provided and summarises the main lessons drawn from privatisation. Previous research including empirical studies comparing the performance of government owned companies, empirical studies in developed countries (non-transition economies), and in developing countries (transition economies) as well as empirical studies comparing pre and post privatisation performance changes are comprehensively discussed.